STRENGTHENING THE PROFILE OF PANCASILA STUDENTS THROUGH DIFFERENTIATED LEARNING IN SOCIAL STUDIES SUBJECTS - Rusmaniah, Rusmaniah; Annisa, Nur; Sari, Raihanah; Handy, Muhammad Rezky Noor; Abbas, Ersis Warmansyah (International Conference On Social Science Education, 2024)
This study aims to explore the strengthening of the Pancasila Student Profile through the implementation of differentiated learning in social studies subjects in class VII of SMPN 11 Banjarmasin. Using a qualitative approach, the research involved classroom observations, interviews with teachers, principals and students, and analysis of learning documents. The results showed that the differentiated learning implemented was able to increase student participation and adapt learning methods to individual needs. In addition, the integration of Pancasila values in the social studies curriculum succeeded in shaping better student characters, such as tolerance, cooperation and social care. The findings show that differentiated learning not only improves academic outcomes, but also contributes to students' character development in line with national education goals. Thus, the implementation of this strategy is recommended as an effort to create a generation with Pancasila character.